DINÂMICA E PROJEÇÃO DIAMÉTRICA EM REMANESCENTE DE FLORESTA OMBRÓFILA MISTA NA FLONA DE SÃO FRANCISCO DE PAULA, RS - EBLING, ANGELO AUGUSTO (2012)
The studies of dynamic processes in natural forests are essential to understand the functioning of plant communities, to the elaboration of sustainable management plans, and to recover and restore degraded areas. The present study aims to analyze the dynamics of an Araucaria Forest fragment in São Francisco de Paula, RS. Data from continuous forest inventory was used, with permanent of one hundred plots, sampling organized in clusters of 100 x 100 m, measured annually from the year 2000 up to 2009. Individuals with diameter at breast height equal or greater than 9.5 cm (DBH ≥ 9.5 cm) were identified and had their dendrometric information measured, considering the recruitment and mortality for the same period. Forest structure and its interaction with local meteorological data were evaluated and performed the projection of the diameter distribution of the forest. The results showed that the forest had not major changes in its structure during the evaluated period. It was found a high density (DA = 787 ind/ha) and Dominance (DoA = 46.13 m²/ha), high values related to the Shannon diversity index (H' = 3.71 nats/ind), Simpson dominance (D = 0.96) and Pielou evenness (J' = 0.79). Mortality rates exceeded recruitment, suggesting a gradual reduction of individuals and basal area increment, indicating the maturation of the forest fragment. The forest showed an intermediate growth compared to other fragments (PDI = 0.126 cm/year). Araucaria angustifolia was the most important species in the forest, with intermediate growth ( = 0.152 cm/year) and its diametric projection demonstrates a stagnant structure, with gradual reduction of its individuals over time. The species with highest growth potential was the Cinnamomum glaziovii ( = 0.332 cm/year), and the diameter projection of the Lauraceae family showed its increasing importance in the forest over time. Growth rates, recruitment and mortality showed plasticity over the sampled period, presenting correlation with the rainfall data, in which the lower growth rates and higher mortality coincided with less rainfall records. In general, the climatic conditions influenced the behavior of the forest, however, did not inhibited his advancement of succession, which increasingly sets its primary composition.